Daya Hambat Trichoderma sp. terhadap Patogen yang Berasosiasi dengan Daun Tanaman Tomat (Lycopersicum esculentum MILL.) - Asniah, Asniah; Wahyuni, Wahyuni; Taufik, Muhammad (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
The study aimed to evaluate the inhibition of Trichoderma sp. associated with the leaves of the tomato plant (Lycopersicum esculentum Mill.). The research was carried out at the Plant Protection Laboratory of the Phytopathology Unit, Faculty of Agriculture, Halu Oleo University, Kendari. The study was arranged using a completely randomized design (CRD) with three types of pathogens, namely Collethotrichum sp., Schlerotium sp., and Paesilomyces sp., repeated five times. Observation parameters were the percentage of inhibition through multiple culture tests, secondary metabolites of volatile compounds, and nonvolatile compounds. The results showed that the ability to inhibit the fungus Trichoderma sp. against the fungal pathogen Colletotrichum sp. able be inhibited by 74.14% and 81.42% respectively in the volatile and nonvolatile secondary metabolite tests, while against the pathogen Sclerotium sp. able to be inhibited by 58.50% in the multiple culture test.